Online Access to the Catalogue and Bibliography of Cartographic Materials of the National Library of Poland (NLP) - Szaniawska, Lucyna (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
Access to information about cartographic materials in the National Library of Poland has been improved by new functionalities intended to keep up with users’ new needs and technological trends. From mid-January 2010 on readers of maps and atlases kept in the library can find catalogue descriptions of these materials through the special website. Three different forms of access to descriptions of cartographic materials are available on the website: (1) Catalogues/Catalogues online — database search in the central computer catalogue of the National Library of Poland (NLP); (2) Bibliographies online. Cartographic documents [download .pdf files — in Polish]; (3) Bibliographies online. Cartographic documents [search database] — access to the database in the MAK system containing items from the published bibliography of cartographic materials.